Effects of Fibre Configuration on Mechanical Properties of Banana Fibre/PP/MAPP Natural Fibre Reinforced Polymer Composite - Amir, N. (Elsevier Ltd, 2017)
Natural fibre reinforced polymer matrix composite (PMC) is one of the advanced technologies developed in the materials engineering industry. Amongst the advantages of natural fibre reinforced PMC are biodegradable, recyclable, lightweight, low production cost, and readily available. Therefore, natural fibre reinforced polymer composites have been used for many applications such as automotive components, aerospace parts, sporting goods and building industry. In this research, high performance polypropylene (PP) composites, using continuous banana fibre as reinforcement with polymer to fibre by weight percent ratio of 70:30, were developed. This research aims to investigate the effects of different configurations of continuous banana fibre reinforcement on mechanical properties of the composite materials. Coupling agent, which is maleic anhydride grafted polypropylene (MAPP) is added to the composites to improve bonding between the polymer matrix and the natural fibre. To further improve the PMC's mechanical properties, banana fibre's configurations are varied, in which their performance are tested. The banana fibre is varied by three different configurations; raw banana fibre, banana fibre yarn, and banana fibre mat. Mechanical properties of the composite samples were assessed using tensile and flexural testing in accordance to ASTM D638 and ASTM D790, respectively. Microstructural analysis was performed by using scanning electron microscope to explain the failure mechanisms and behavior of the composites. This study has enabled ranking of different banana fibre configurations towards mechanical properties of the natural fibre reinforced thermoplastic-based composites. Morphology examination of the fracture surfaces confirmed failure mechanisms and explained why one fibre configuration is superior to the others. © 2017 The Authors.